The INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY ON EMPLOYEE PERFORMANCE AT THE WESTIN JAKARTA HOTEL - Octarina, Dian; Sinaga, Rheinerr; Fitri, Alissa; Putriaisyah, Virka (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
Occupational health and safety is an important factor that influences employee performance, especially in the hotel sector which has high risks related to interaction with guests and use of equipment. This research aims to examine the influence of K3 on employee performance at The Westin Hotel Jakarta. The method used is quantitative research with a simple regression approach. The research sample consisted of 40 employees selected by accidental sampling, with data collected using a questionnaire which was measured using a Likert scale. The results of partial hypothesis testing show that occupational health and safety have a significant effect on employee performance. This shows that good implementation of occupational health and safety can increase employee motivation, efficiency and work quality. Based on the research results, it is recommended that employees continue to participate in occupational health and safety training and actively provide input regarding its implementation. Hotel management is also advised to strengthen occupational health and safety policies through regular training, provision of personal protective equipment, and regular evaluations to ensure consistent implementation. With these steps, it is hoped that employee performance can improve so as to create a more productive and safe work environment.